Meningkatkan kemampuan berbahasa inggris menggunakan metode Roleplay (bermain peran) untuk siswa kelas IV antara Mahasarakham University Demonstration School (Elementary) di Thailand dengan SDS Nurul Huda di Indonesia - Widyani, Hanna Nazhifa; Fatihaturosyidah, Fatihaturosyidah; Alfarisa, Fitri; Sutarjo, Ajo; Matwangsaeng, Pennapa (Universitas Muhammadiyah Magelang, 2024)
Humans will use these language skills to develop communication skills that will be used in interacting with other people. One communication skill that is no less important is speaking skills. In addition to students' lack of vocabulary, their lack of confidence in speaking and assessing English as a difficult subject makes speaking a difficult language skill. It is hoped that this research can make a contribution to the world of education, especially in designing learning plans that are tailored to the characteristics and abilities of each student. This research uses the PTK (Classroom Action Research) method. This research will use 2 classes, namely class 4/1 ESC MUDS Thailand and class 4A SDS Nurul Arafah. From this research it was found that the English communication skills of Thai students were 80%, while Indonesian students were still less than 50%. From the application of this role play method, students become accustomed to role playing activities using English. The effects that occur on students are student courage, student self-confidence, student voice volume, vocabulary, understanding, fluency and other aspects of students increase. , the sense of cooperation with group friends was more visible in the second cycle compared to the first cycle because students were getting used to working in groups. This can be seen from the results of observations by researchers and observers in each cycle.